Biodigestão anaeróbia do bagaço da cana-de-açúcar utilizando excretas de frango como inóculo - Ibrahim, Samy Barros Souza (2016)
The search for renewable sources of energy sets the sugarcane as important energy sources. The bagasse generation of this input shows a high potential for the production of sustainable energy waste. Aiming to make better use of this product, this study evaluated the anaerobic production of biogas generated by bagasse from sugarcane when used as chicken excreta inoculum in experimental anaerobic reactors batelados type. six reactors, divided into two treatments were used. The first consists of bagasse sugarcane in natura (03 reactors) and the second consisting of bagasse sugarcane treated with NaOH (03 reactors). In both treatments are used as inoculum chicken excreta. The time, in days, of reading the generated gas was 54 days. It was observed that the potential energy of sugarcane bagasse had the point of greatest methanogenic activity approximate days in the twenty-fifth and twenty-sixth, respectively for each treatment, Treatment 2, obtained the best result, producing double CH4 methane in virtually the same time period.